AB0823 Age at Disease Onset Helps to Further Characterize the Disease Phenotype in Psoriatic Arthritis. (9th June 2015) - Queiro, R.; Morante, I.; Cabezas, I.; Acasuso, B.; Tejόn, P.; Alperi, M.; Riestra, J.L.; Arboleya, L.; Ballina, J.
Abstract : Background: The age of onset of psoriasis has been used for decades as an appropriate descriptor to define two subpopulations of psoriatic patients (types I and II). Clinical features of both types of psoriasis have been clearly delineated. However, the importance of this distinction in patients with psoriatic arthritis (PsA) has not been studied in depth. Objectives: To evaluate the importance of age of onset of both psoriasis and arthritis in dissecting the clinical features of PsA. Methods: This cross-sectional study included 205 patients with PsA (CASPAR criteria) seen at a single university institution. Socio-demographic, clinical, radiographic, and laboratory variables were included and population was then stratified according to age at onset of psoriasis, as well as joint manifestations, in two groups: early-onset and late -onset, according to a cut off value of 40 years old. Uni and multivariate analysis were performed. All patients gave informed consent. This study was approved by an institutional ethics committee. Results: Early-onset psoriasis (EOP) showed extensive skin involvement (OR 2.3, p=0.011), higher prevalence of axial pattern as disease onset (OR 4.6, p=0.009) and mixed pattern during evolution (OR 2.4, p=0.019), increased frequencies of family history of both psoriasis (OR 3.1, p=0.003) and PsA (OR 4.0, p=0.021), higher prevalence of HLA-C*06 (OR 2.03, p=0.03) and HLA-B*27 (OR 2.7, p=0.02). Early onset arthritis (EOA) patients presented more family history of PsA (OR 2.9, p=0.007), as well as HLA-B*27 positivity (OR 5.9, p<0.0001). Patients with late-onset arthritis (LOA) had more DM (OR 4.0, p=0.009), hypertension (OR 2.5, p=0.004), dyslipidemia (OR 2.3, p=0.011), and obesity (OR 1.7, p=0.012). Late-onset psoriasis (LOP) showed more obesity (OR 1.9, p=0.035), DM (OR 9.4, p<0.0001), hypertension (OR 4.1, p<0.0001), and ischemic heart disease during follow-up (OR 5.9, p=0.021). In multivariate analysis, LOP predicted DM development (OR 12.1; CI: 2-73.1, p=0.006). Likewise, LOA was shown to be an independent risk factor for hypertension (OR 5.2; CI: 1.09-25.02, p=0.039). Conclusions: Age at disease onset is a key stratification factor to better characterize the clinical and cardiovascular risk profile of psoriatic disease. In psoriatic disease, diabetes risk seems to be related to age at skin disease onset whereas hypertension development appears linked to age at joint disease onset. Both conditions are more prevalent in late disease. References: Queiro R, Tejόn P, Alonso S, Coto P. Age at disease onset: a key factor for understanding psoriatic disease. Rheumatology (Oxford) 2014; 53:1178-85. Disclosure of Interest: None declared